Visual Electrodiagnostic Testing in Birdshot Chorioretinopathy - Radouil Tzekov; Brian Madow (Journal of Ophthalmology)
Birdshot chorioretinopathy (BSCR) is a rare form of autoimmune posterior uveitis that can affect the visual function and, if left untreated, can lead to sight-threatening complications and loss of central vision. We performed a systematic search of the literature focused on visual electrophysiology studies, including electroretinography (ERG), electrooculography (EOG), and visual evoked potentials (VEP), used to monitor the progression of BSCR and estimate treatment efficacy. Many reports were identified, including using a variety of methodologies and patient populations, which makes a direct comparison of the results difficult, especially with some of the earlier studies using nonstandardized methodology. Several different electrophysiological parameters, like EOG Arden’s ratio and the multifocal ERG response densities, are reported to be widely affected. However, informal consensus emerged in the past decade that the full-field ERG light-adapted 30 Hz flicker peak time is one of the most sensitive electrophysiological parameters. As such, it has been used widely in clinical trials to evaluate drug safety and efficacy and to guide therapeutic decisions in clinical practice. Despite its wide use, a well-designed longitudinal multicenter study to systematically evaluate and compare different electrophysiological methods or parameters in BSCR is still lacking but would benefit both diagnostic and therapeutic decisions.